(NoSW)QÆTA EKOBEZPE^NOGO ÆNFORMACÆJNOGO SUSPÆLXSTWA(B: (NPROBLEMI Æ PERSPEKTIWI (B/s)E - (NsA)QÃNKO(B, (Nt(B. (Nw(B.,s)E; (NzADWORNIJ(B, (Ns(B.(Nw(B.,s ((NkI)QÇW (B:s)E (NoSW)QÆTA uKRAÇNI(B,s)E, 2008)
(NrOZKRITO PITANNQ OSW)QÆTI MAJBUTNXOGO KRÆZX NINÆ[NYJ ÇÇ STANs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NoSW)QÆTAs)E; (NeKOLOG)QÆQ OSWÆTIs)E -- )Qæ(NNFORMACÆJNE SUSPÆLXSTWOs)E; (NOSW)QÆTAs)E; )QÆ(NNFORMACÆJNE SUSPÆLXSTWOs)E; (NEKOLOG)QÆ^NA OSWÆTAs)E; (NEKOLOG)QÆ^NE MISLENNQs)E